Comparação entre os métodos estáticos com o ensaio de carregamento dinâmico de previsão de capacidade de carga em estacas pré moldadas de concreto - Oliveira, Andressa de (2015)
This work is an examination of a construction site located in Curitiba / PR in safety and ergonomics, with reference to the current regulations in force in Brazil. Through a qualitative case study, it demonstrates the financial advantage of properly following regulatory procedures, compares the costs of noncompliance and the appropriateness of the financial impact of their penalties. The main results were that the values of the adjustments were much more viable than the value of the penalties. This research aims to be relevant to workers and managers, business and academic area with an interest in quality of work on site, it is a field that still has a lot to develop in the Construction Industry.